Statistical optimisation of operational parameters using response surface methodology and phytoremediation of arsenic in constructed wetland - Rahman, Md Ekhlasur; Shamsuzzaman, S. M.; Mahmud, Khairil; Uddin, Md Kamal; Abd Ghani, Siti Salwa; Abd Shukor, Mohd Yunus; Sadeq, Buraq Musa; Chompa, Sayma Serine; Akter, Amaily; Nabayi, Abba; Halmi, Mohd Izuan Effendi (Taylor and Francis, 2025)
Phytoremediation using the robust perennial grass Pennisetumpurpureum has been researched as a substitute for traditional treatment approaches for arsenic (As) pollution remediation in the Constructed wetland system. In the current investigation, As absorption and removal through P. purpureum were measured and optimisation was done using Response surface methodology (RSM). To maximise the absorption and removal of As, the Box-Behnken design (BBD) was applied, with 3 key factors (As concentration in treatment sand: 5, 22, and 39 mg kg−1; exposure period: 14, 28, and 42 days; aeration rate: 0, 1, and 2 L min−1) in the optimisation. The estimated optimum conditions were 39 mg kg−1 As concentration, 42 days of retention time, and 0.18 L min−1 aeration rate, with an actual biological As accumulation and removal were 5,088.19 mg kg−1 dry weight (DW) and 91.45%, respectively. These amounts were comparable to the amount predicted through RSM 5,245.94 mg As kg−1 DW and 94.29%, respectively. The variance between the test and expected results was 3.10%, demonstrating that RSM could estimate the optimum biological accumulation of As correctly with relatively minimum error. Factors, like As concentration, retention time, and aeration rate, could influence the performance of arsenic phytoremediation through P. purpureum.